El tercer sector frente a las transformaciones del Estado de Bienestar - Rubio García, José Antonio (Cuadernos de Trabajo Social, 2007)
The civil society is taking on a higher importance as one of the social political speakers, not only for the political and economical institutions but also for the public opinion. Organisations that take part of the Civil Society are identified as Third Sector because they are between the State and the market. Taking in account the big crisis of the welfare state, the third sector has become a producer of social welfare, offering the social services that the State is not able to provide. In this context, the different social actors have different ideological positions and followed strategies about the roll that the third sector should play in societies.